Transcriptomic and Reverse Genetic Analysesof Branched-Chain Fatty Acid and Acyl Sugar Production in Solanum pennellii and Nicotiana benthamiana - Steve Slocombe (Plant Physiology, 2008)
Acyl sugars containing branched-chain fatty acids (BCFAs) are exuded by glandular trichomes of many species in Solanaceae, having an important defensive role against insects. From isotope-feeding studies, two modes of BCFA elongation have been proposed: (1) fatty acid synthase-mediated two-carbon elongation in the high acyl sugar-producing tomato species Solanum pennellii and Datura metel; and (2) alpha-keto acid elongation-mediated one-carbon increments in several tobacco (Nicotiana) species and a Petunia species. To investigate the molecular mechanisms underlying BCFAs and acyl sugar production in trichomes, we have taken a comparative genomic approach to identify critical enzymatic steps followed by gene silencing and metabolite analysis in S. pennellii and Nicotiana benthamiana. Our study verified the existence of distinct mechanisms of acyl sugar synthesis in Solanaceae. From microarray analyses, genes associated with alpha-keto acid elongation were found to be among the most strongly expressed in N. benthamiana trichomes only, supporting this model in tobacco species. Genes encoding components of the branched-chain keto-acid dehydrogenase complex were expressed at particularly high levels in trichomes of both species, and we show using virus-induced gene silencing that they are required for BCFA production in both cases and for acyl sugar synthesis in N. benthamiana. Functional analysis by down-regulation of specific KAS I genes and cerulenin inhibition indicated the involvement of the fatty acid synthase complex in BCFA production in S. pennellii. In summary, our study highlights both conserved and divergent mechanisms in the production of important defense compounds in Solanaceae and defines potential targets for engineering acyl sugar production in plants for improved pest tolerance.